Role of Social Teacher in Forming of Vital Competence of Children of 6–7 Years of Age - Olena Sas (Pedagogical Discourse, 2012)
The content of activity of social teacher and its influence onto the forming of vital competence of children of 6–7 years of age has been revealed in the article; the analysis of scientific researches and normative documents has been given.